The effects of environmental (cadmium) and pharmacological (CBD and THC) chemicals in the spermatogenic process - Silva, Janaina da (2021)
A significant trend towards a worldwide decline in human male fertility has been reported over the last years. In the meantime, exposure to chemicals has been proposed to potentially contribute to male reproductive disorders, in which environmental and pharmacological/recreational chemicals might induce detrimental effects on male reproductive health. Among a complex variety of environmental chemicals, cadmium (Cd) is one of the heavy metals that rank among the priority metals that are of public health significance, since Cd is considered as an endocrine disruptor. Human beings are daily exposure to Cd through occupational (e.g. production of batteries) and non-occupational (e.g. contaminated food/water, cigarette smoke) sources. Furthermore, cannabis consumption for medical and recreational purposes is on the rise. In this context of chemicals and male fertility, exposure to cannabis compounds, called phytocannabinoids (cannabinoids), could result in adverse outcomes to male reproductive health. So, this present thesis aimed to assess the impact of these two global trends, cadmium and cannabinoids, in the spermatogenic process. It is already known that cadmium induces damage to the testis. However, the mechanisms that cadmium leads to testicular histopathologies and the relationship between dose, route, and time of exposure and injuries are poorly understood. In this sense, we conducted a systematic review (Chapter 1) to answer these questions. After retrieving original studies on databases, we organized the results into an Adverse Outcome Pathway (AOP) framework. Also, a bias analysis was performed. In the 37 studies selected, it was clear that cadmium induces significant histopathologies in the murine model’s testis regarding routes, in a dose- and time-dependent manner. The damages can be observed in the first hours of exposure, mainly vascular damages suggesting that vasculature failure is the primary mechanism involved. The AOP showed that potential molecular initiating events may mimic and interfere with essential elements disrupting proteins (structural and antioxidants), change in the oxidative phosphorylation enzyme activities, and gene expression alteration, which lead to reproductive failure. However, analysis of bias showed that the current evidence presents poor methodological quality. Regarding the cannabinoid impact on male reproductive health, we performed two biological essays. In one manuscript (Chapter 2), we aimed to answer whether the two main phytocannabinoids present in cannabis could represent a hazard for adult human testis. For that, we exposed adult human testis to Δ 9 -tetrahydrocannabinol (THC), cannabidiol (CBD), or CBD/THC (ratio 1:1) at the concentrations from 10 -9 M to 10 -5 M for 48 hours, by using our unique ex vivo model of organotypic culture. Our findings show no alteration in testis histology, testosterone production, number of apoptotic and proliferative cells, and expression of some genes encoding important testicular proteins. Since some male reproductive problems have been hypothesized to have a fetal origin, in the last study (Chapter 3), we assessed whether prenatal exposure to CBD and THC could lead to male reproductive disorders in adult life. For that, we exposed pregnant mice from embryogenic day 6.5 (E6.5) to E15.5 to 5mg/kg/day of CBD/THC (ratio 1:1), by gavage. Then, we observed decreased testicular weight and testicular morphological alterations identified by morphometric analyses in adult offspring. However, these alterations were not followed by changes in the undifferentiated spermatogonia and Sertoli cell numbers. The gene expression analysis revealed an increase in the expression of pro-apoptotic (Bax), germ cell differentiation (Sohlh1), and regulating meiotic (Stra8) genes. Alterations in the serum testosterone levels were not observed. In general, our findings demonstrate that cadmium, an environmental pollutant, can affect the male reproductive health of murine models and lead to male infertility. On the other hand, the two main cannabinoids present in cannabis, THC and CBD, which are also used as pharmacological chemicals, do not cause acute direct effects in the testicular histophysiology using our well-characterized organotypic culture of adult human testis. However, prenatal exposure to a mixture of these cannabis-derived cannabinoids can lead to decreased testis weight of mice in adult life. Also, prenatal exposure can accelerate meiosis and cellular differentiation and induce apoptosis, based on the molecular findings, probably, contributing compensatory to the decreased testis weight. So, in mice, prenatal exposure to a mixture of THC/CBD might affect the testis biology of adult offspring. Overall, the results presented by this thesis provide new insights into male repro-toxicology and reproductive health, which might be considered to preserve fertility across the population. Keywords: Repro-toxicology. Environmental contaminant. Adverse Outcome Pathway. Δ 9 - tetrahydrocannabinol. Cannabidiol. Organotypic culture.